PERBEDAAN SUDUT SNA, SNB, MPSN DAN RELASI GIGI ANTERIOR ANTARA SEBELUM DAN SESUDAH PERAWATANANTERIOR CROSSBITE TIPE DENTAL DENGAN PESAWAT HAWLEY (Kajian Sefalometri pada anak usia 9-10 tahun di Fakultas Kedokteran Gigi Universitas Sumatera Utara) - , Silvia Loren; , Dr. drg. Indah Titien S., SU., Sp.KGA(K) ([Yogyakarta] : Universitas Gadjah Mada, 2011)
Anterior crossbite was a condition where the maxillary incisors occlude lingually to the mandibular incisors. Dental type anterior crossbite often occured in children. It was recommended that dental type anterior crossbite managed early to avoid prolonged treatment in permanent dentition. The purpose of this study is to determine the differences between SNA, SNB, MPSN, anterior teeth relation before and after treatment of dental type anterior crossbite. This is an quasi experimental study with cross sectional design. Subjects were 12 children aged 9-10 years treated in Orthodontic Departement of Dentistry Faculty in North Sumatera University with dental type anterior crossbite. Each of them were taken the cephalometric radiograph to determine the SNA, SNB, MPSN, overbite and overjet. Paired t-test showed that there was difference in SNA, MPSN before and after dental type anterior crossbite treatment (p<0.05), while the SNB angle showed no significant difference before and after treatment of dental type anterior crossbite (p> 0.05). Key Words : dental type anterior crossbite, cephalometry, SNA, SNB, MPSN, overbite, overjet. xvi A total of 91,67% subjects reached normal overbite and 75% reached normal overjet after dental type anterior crossbite treatment. The conclusion was the treatment of dental type anterior crossbite influenced to the angle of SNA and MPSN angle, 91,67% subjects reached normal overbite and 8,33% have not reach normal overbite. 75% reached normal overjet and 25% have not reach normal overjet after dental type anterior crossbite treatment.overjet and overbite correction but there was no difference in SNB angle before and after dental type anterior crossbite treatment.